Application of the Project Based Learning Model in Natural and Social Science Subjects to Increase the Activeness of Class IV Students at SD Sumoroto 02 Ponorogo Regency - Vigit, Andik Angga (BASICA Journal of Arts and Science in Primary Education, 2023)
Primary education in elementary schools (SD) serves as the foundation for various fields of knowledge to be further developed in subsequent phases. In Indonesia, one of the mandatory subjects in elementary schools is Natural and Social Sciences (IPAS). IPAS is an abstract subject that tends to be challenging for students to comprehend. This research aims to enhance the students' engagement through the implementation of the Project Based Learning (PjBL) model in Grade IV students at SD Sumoroto 02, Ponorogo Regency. The study follows a Classroom Action Research (PTK) approach involving 16 students and is conducted during the even semester of the 2022/2023 academic year, focusing on the topic of Changes in the Form of Payment Instruments. The research employs a quantitative method, utilizing descriptive analysis of percentage data. Data collection techniques involve observing student engagement and administering questionnaires on the implementation of Project Based Learning. The research findings reveal that during the pre-cycle phase, only 18.75% of students were actively engaged in the classroom. However, after implementing the Project Based Learning model in Cycle I, the percentage of actively engaged students increased to 81.5%. In Cycle II, it further increased to 87.5%. These results indicate a significant improvement in student engagement through the implementation of the Project Based Learning model. Based on the positive student response, it can be concluded that the Project Based Learning model has been successfully implemented in IPAS instruction at the elementary school level